Puccinia stylosanthis on Stylosanthes spp. in Brazil - Lenné, Jillian M.; Sousa Costa, N.M. de (Scientific Societies, 1985)
Rust caused by Puccinia stylosanthis is reported for the first time on native populations of Stylosanthes aurea and S. guianensis var. pauciflora in the vicinity of Diamantina, Minas Gerais, Brazil. Although not common in May 1983, rust severely affected 50% of S. aurea and moderately affected most S. guianensis var. pauciflora plants in May 1984. Because the latter species is a promising tropical forage legume in the savannas of Brazil and Colombia, the need to evaluate existing germ plasm collections for rust resistance is stressed.